Towards Enacting Social Justice in HE: : A Case of Postdoctoral Research Fellows - Moyo, Zvisinei; Perumal, Juliet (International Journal of African Higher Education, 2020)
The purpose of this review was to unearth the challenges of postdoctoral research fellows who are classified neither as staff nor students. It provokes research to rethink measures to support this group of academics who have been neglected. Three central questions guided this review: What are the common themes in literature and research on PRDF? What social justice issues arise from the PDRF literature? How can this literature and conceptualisation inform management of PDRFs in terms of social justice? A total of 45 publications were reviewed. The full text of the systematically identified studies were stored in a marked folder on a computer desktop and screened through examining topics and abstracts. Each of the studies was analysed to come up with six themes which were discussed through the lens of social justice, followed by a suggestion for further discussion in the field. The literature portrays a culture that has undermined issues and concerns of social justice. Universities are required to imagine new directions for future research, challenged to become activists and take a pro-justice stance to transform the culture, practices and procedures to benefit the marginalised. Universities can utilise these suggestions as a guide to evaluate their efforts and programmes.